The exponential equation `3^(2x+1)=243` has to be solved

`3^(2x+1)=243`

=> `3^(2x + 1) = 3^5`

As the base is the same equate the exponent

2x + 1 = 5

=> 2x = 4

=> x = 2

**The solution of the equation is x = 2**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now